2020
DOI: 10.1080/15592294.2020.1853319
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study for glyphosate induced transgenerational sperm DNA methylation and histone retention epigenetic biomarkers for disease

Abstract: The herbicide glyphosate has been shown to promote the epigenetic transgenerational inheritance of pathology and disease in subsequent great-grand offspring (F3 generation). This generational toxicology suggests the impacts of environmental exposures need to assess subsequent generations. The current study was designed to identify epigenetic biomarkers for glyphosate-induced transgenerational diseases using an epigenome-wide association study (EWAS). Following transient glyphosate exposure of gestating female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…These results support previous works that found adverse effects related to fetal parameters and structural congenital anomalies after perinatal exposure of GBH (F0) in secondgeneration of rats (F2) (76,82,83). However, Deepika Kubsad et al (41) and Maamar et al (42) reported for the first time that transgenerational inheritance of disease in rodents could be produced by DMRs and DHRs in the male germline, and these sites could potentially act as a biomarkers for specific diseases. Based on these findings, further studies are needed to deepen on the generational toxicology of glyphosate, in the disease etiology of the future generations.…”
Section: Glyphosate Induced Epigenetic Transgenerational Inheritancesupporting
confidence: 90%
“…These results support previous works that found adverse effects related to fetal parameters and structural congenital anomalies after perinatal exposure of GBH (F0) in secondgeneration of rats (F2) (76,82,83). However, Deepika Kubsad et al (41) and Maamar et al (42) reported for the first time that transgenerational inheritance of disease in rodents could be produced by DMRs and DHRs in the male germline, and these sites could potentially act as a biomarkers for specific diseases. Based on these findings, further studies are needed to deepen on the generational toxicology of glyphosate, in the disease etiology of the future generations.…”
Section: Glyphosate Induced Epigenetic Transgenerational Inheritancesupporting
confidence: 90%
“…Until now, numerous studies have been performed to investigate the genotoxicity, mutagenicity, and cell viability of glyphosate in different types of human cells (Mañas et al, 2009; Nagy et al, 2019). As we know, only a few studies have investigated global and gene-specific methylation alteration in response to glyphosate (Ben Maamar et al, 2020; Kwiatkowska et al, 2017; Woźniak et al, 2020). In the study, 0.25 mM concentration of glyphosate was reported to cause a decrease in the total amount of m 5 C. In addition, the levels of m 5 C in p16 and p53 genes significantly increased compared to the negative control.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, adverse pregnancy outcomes were reviewed but no significant link was reported between an increase in hypospadias, anencephaly, preterm delivery, birth weight, and exposure to G or R. However, exposure to G during the pre-conception period was related to late abortion. G has been detected in farmers' urine in the µg/L range as well as in farmers' children's urine, but at lower concentrations [95].…”
Section: In Vivo Studiesmentioning
confidence: 94%
“…Researchers have evaluated the adverse pregnancy outcomes due to exposure to G. De Araujo et al [95] reported a non-significant association between G or GBH parental exposure and an increase in hypospadias, anencephaly, gastroschisis, preterm deliveries, congenital anomalies, and birth weight. There was a possible link between G exposure during preconception and the risk of late abortion [91].…”
Section: Involvement Of Glyphosate or Gbh In Reproductive Pathologiesmentioning
confidence: 99%